Cerita Rakyat Berbasis Potensi Lokal untuk Adaptasi Sosial Anak Generasi Alfa di Kabupaten Kudus - ., Suryaningsih; ., Wagiran; Supriyanto, Teguh (Jurusan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2022)
Folklore contains elements of language, ethnicity, and local potential. These three elements affect the human community. This is needed for social adaptation, especially for children in the phase of psychological development. The goal is to interact socially, get to know ethnicity and find habits of life. This kind of local potential contains the right stimulation to be studied. Through the single exponential smoothing method in an adaptive approach, the alpha generation is able to recognize the wisdom of their area, Kudus district. Developments in the geographical context, Pancasila values, and healthy living are things that are developed in the structure of the story. However, the development still considers the authenticity of the story source. The three research results include the composition of the Bulusan folklore book with animative nuances that are adapted to local potential, the response of the millennial generation of 81%, and the sustainability of the book concept for its interest until 2024. Conclusions about whether there is no animation element that contains Pancasila values ​​and local potential need to be made every year. 3 years for maximum effect. Keywords: Folklore, social potential, social adaptation, alpha generation children